Exploring Spelling Errors among College Students - Karim Jawhar Karim; Salam Nawkhosh Bakir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This study is entitled exploring Spelling Errors among college students. This research aims at analyzing kinds of errors, shown gender differences in doing spelling errors, find potential reasons behind the spelling errors among the university students and recommend some ways in which spelling can be improved for Central Kurdish EFL learners in addition to being taught more effectively by their teachers. The quantitative method of investigating the spelling errors of fifty central Kurdish learners from the final year of English department at college of basic education – Salahaddin University are being studied by utilizing two tests multiple choice and dictation both genders were participated. Findings represent that Phonological knowledge of first language of students, differences in writing system between first language and foreign language, Recklessness and lack of knowledge by the students, carelessness and insufficient knowledge about the words they write, lack of knowledge in English writing system, interference of the mother tongue and its spelling rules have been the issues for their errors. Many English words have silent alphabets in their spellings and a lack of knowledge of correct pronunciation of English words are the reasons behind committing spelling errors. Basis on findings it is recommended that the instructors are advised to relate problematic of spelling errors to students’ mother language to draw their attention to the fact that there are many differences between both of them in writing system, direction, sound system, number of letters, orthography...etc.